ANALYSIS OF EFFORTS TO SUPERVISE THE DISTRIBUTION OF ILLEGAL DRUGS BY THE FOOD AND DRUG SUPERVISORY AGENCY (BBPOM) OF PEKANBARU CITY - Sela Gustiana; Ikhwani Ratna (Yayasan Wayan Marwan Pulungan, 2025)
This research is motivated by the existence of illegal drugs or drugs without distribution permits in circulation. There are two objectives in this study, namely: 1) to determine the supervision of the Pekanbaru City BBPOM in eradicating illegal drugs, 2) to determine the factors that influence the circulation of illegal drugs in Pekanbaru City. This type of research uses a qualitative descriptive method, with interview data collection techniques, observation and documentation studies. The informants of this study consisted of the Head of the BBPOM Inspection Distribution Facility Team, Young Expert Pharmacy and Food Employees (PFM) of BBPOM, and the community. The results of the study indicate that the supervision of illegal drugs carried out by BBPOM in Pekanbaru is not optimal. BBPOM in Pekanbaru carries out the function of supervision before circulation which includes setting drug standards, drug safety and supervision after distribution which includes monitoring and assessment actions and taking corrective actions. In addition, BBPOM also cooperates with related agencies including the Police, Customs, and the Health Service. However, there are still several obstacles including the lack of human resources, the intensity of supervision that is not yet effective and the lack of participation and awareness from the community